SWOT Analysis to Determine a Creative Economic Development Strategy During the Covid-19 Pandemic - Sulasih Sulasih; Weni Novandari; Suliyanto Suliyanto; Fera Agus Dwiyaningsih (International Journal of Ecma Science, 2021)
In the condition of the outbreak of the covid-19 pandemic, many people have lost their jobs because the government has implemented Large-Scale Social Restrictions (PSBB) and social distancing policies in all regions in Indonesia which have an impact on the economic decline, and many companies are laying off workers. but in the bird cage craft industry, Jaya continues to produce bird cage crafts and does not carry out Termination of Employment (PHK) on employees. The bird cage craft industry is one of the business actors in the creative economy sector. In a business, of course, there are internal and external company problems that have an impact on a business. This study aims to find out what strategies can develop the Creative Economy of jaya bird cage crafts during the Covid-19 pandemic. The research conducted is a field research with the research location in Banjarsari Village in November 2020-June 2021. The data collection method is in the form of interviews, observation and documentation. The data analysis technique used is descriptive qualitative analysis which includes data reduction, data presentation and conclusions. To systematically identify various factors and formulate a company's strategy using SWOT analysis. The results of this study indicate that the Creative Economy development strategy during the covid-19 pandemic of the jaya bird cage industry is to continue to increase production, increase bookkeeping and skill training for employees, improve product quality, and increase promotions using various social media. With the creative industry of the Jaya Bird Cage craft, it adds to the contribution to aspects of people's lives